Pituitary-Derived Circular RNAs Expression and Regulatory Network Prediction During the Onset of Puberty in Landrace × Yorkshire Crossbred Pigs - Chen, Zitao; Pan, Xiangchun; Kong, Yaru; Jiang, Yao; Zhong, Yuyi; Zhang, Hao; Zhang, Zhe; Yuan, Xiaolong; Li, Jiaqi (Frontiers in Genetics, 2020)
Being the center of the hypothalamus-pituitary-ovary (HPO) axis, the pituitary plays a key role in the onset of puberty. Recent studies show that circular RNAs (circRNAs) can perform as miRNA sponges to regulate development in animals. However, the function of pituitary-derived circRNAs in first estrus remains unclear in pigs. In this study, we performed a genome-wide identification and characterization of circRNAs using pituitaries from Landrace × Yorkshire crossbred pigs at three stages: pre-, in-, and post-puberty, to describe such pituitary-derived circRNAs in pigs. A total of 5148 circRNAs were found in the gilts’ pituitaries, averaging 18 682 bp in genomic distance, which consisted of approximately 91% exonic, 6% intergenic, and 3% intronic circRNAs. Furthermore, 158 novel circRNAs were identified for the first time and classified as putative pituitary-specific circRNAs. Their expression levels during the onset of puberty, significantly exceeded those of the other circRNAs, and the parental genes of these putative pituitary-specific circRNAs were enriched in “ssc04917: prolactin signaling pathway,” “ssc04080: neuroactive ligand-receptor interaction,” and “ssc04728: dopaminergic synapse” pathways, all of which were consistent with pituitary functioning. Additionally, 17 differentially regulated circRNAs were found and investigated for their potential interaction with miRNAs, along with genes, by constructing a circRNA-targeted miRNA-gene network. Taken together, these results provide new insight into the circRNA-mediated timing of puberty in gilts at the pituitary level.